Optimize effort oil collection in fat pit palm oil factory tanjung seumantoh - Yusmartato, Y; Parinduri, Luthfi; Hasibuan, Abdurrozzaq; ., Ramayulis; Krianto Sulaiman, Oris (International Journal of Engineering and Technology, 2018)
The fat pit is a reservoir and deposition pond of sludge that still contains oil from the condensate disposal of boiling stations and clarification stations that flow through the trenches in gravity. Separation method is done biologically, ie separated oil because of the breaking of oil molecules as a result of fermentation, heating process and deposition process, then the oil will be seen floating on the upper surface because it has a smaller density. The quoted oil is pumped back to the clarification station through a tool called skimmer and oil comb. If the oil con-tent in the mud 0.30% will be pumped into effluent treatment and will be streamed into the river.Â Â